Experimental investigation of liquid interface stability during the filling of a tank in microgravity - Govindan, Sesha N C; Dreyer, Michael E (PANGAEA, 2023)
The storage of propellants in space as well as the transfer and filling of spacecraft tanks is a prerequisite for future long-term space exploration missions. In this work, the vented filling of a partially filled tank, which is envisioned as a spacecraft tank, was investigated experimentally under compensated gravity in the Bremen Drop Tower. Experiments were performed with a partially filled tank and a test liquid HFE-7500. The drop tower provides 9s of compensated gravity. The shape of the free liquid surface inside a right circular cylinder changes from the normal gravity configuration to a free fall configuration during the test. The fillling was initiated after 3.5s and continued until the end at 9s. The interaction of the incoming liquid jet with the liquid interface was studied for different volumetric flow rates. A stable, but not steady liquid interface was characterized by a deformation due to the incoming liquid jet and the formation of a geyser. The growth of the geyser and the following disintegration into liquid droplets indicated an unstable liquid interface. Subcritical, critical and supercritical regimes of the volumetric flow rates were identified to classify stable and unstable liquid interfaces. The critical Weber number was found to be 1.04, which corresponds to a critical volumetric flow rate of 1.30mL/s. This critical Weber number was compared with the existing literature. Additionally, the behaviour of the liquid interface during the reorientation of the liquid inside the tank was observed.
Keywords: Drop tower experiment; Interface stability; Liquid reorientation; Microgravity; Vented filling; Weber number